Nutritional status of adolescents attending the Iranian secondary school in Kuala Lumpur, Malaysia - Zarei, Maryam; Huang, Mary Soo Lee; Mohd Taib, Mohd Nasir; Zarei, Fatemeh (Canadian Center of Science and Education, 2014)
Introduction: The aim or this study was to determine factors associated with body weight status among Iranian adolescents in the two Secondary Schools run by the Embassy in Kuala Lumpur. Methods: A self administered questionnaire was used to assess socio demographic characteristics, physical activity, and body image. Dietary intake was recorded through individual interviews with the researcher. The Physical Activity Questionnaire for children (PAQ-C) was used to evaluate levels of physical activity of the adolescents. Results: One-third (32.2%) of respondents were of normal weight, 14.5% and 11.1% were overweight and obese respectively, while 18.6% and 23.6% were severe thinness and thinness respectively. While the distribution of obese respondents by gender was almost the same, overweight females (16.4%) exceeded overweight males (12.7%) and although more females were in the thinness category (24.7% compared to 22.7%), more males were severely thin (20.0%) compared to 17.1% of the females. Body weight status was significantly associated with age (p < 0.05), gender (p < 0.05) and grade (p < 0.05). Males had significantly higher physically activity scores than females (p < 0.05). Intake of all micronutrients were higher than Dietary Reference Intake (DRI), except for vitamins B1, B2, C, D and E, Folate, Zinc, Magnesium, Potassium, Calcium and Phosphorus. There was a tendency for the females to overestimate their weight and 72.6% of them expressed their desire to lose weight while 60% of the males wanted to gain weight. There was also significant association between body weight status and perception of ideal body size (p = 0.000) and healthy body size (p = 0.000). Conclusion: This study provides some information for the Iranian Secondary school to design intervention programs to improve the body weight status of their students.